Genital tuberculosis mimic as a genital malignancy in post menopausal women - Mahajan, Monalisa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Genital tuberculosis tends to be an indolent infection and the disease may not manifest for year after initial seeding. The most common presentation reported in general population are pelvic pain, postmenopausal bleeding, ascites, abdominal mass, ovarian mass. The diagnosis is made by histopathological examination. Surgery is indicated as presence of abdominal pelvic mass with severe pain. Preoperative diagnosis of genital tuberculosis is often difficult because of confusion with ovarian malignancy. A 60 years old women present with weight loss, palpable abdominal mass with ascites, prominent bilateral ovaries and increase level of CA125. Pelvic malignancy was initially suspected but a diagnosis of tuberculosis was made following postoperative peritoneal wash biopsy. Patient managed with surgical laparotomy under a provisional diagnosis of ovarian malignancy but the final diagnosis was genital tuberculosis followed by anti tubercular regimen. Genital tuberculosis with high level of CA125 mimicking ovarian carcinoma.